2022
DOI: 10.3390/antibiotics11111471
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Surveillance and Meta-Analysis of Antimicrobial Resistance and Food Sources from China and the USA

Abstract: Since the discovery of antibiotics in the 20th century, they have been used to fight against infections. The overuse of antibiotics in the wider environment has resulted in the emergence of multidrug-resistant bacteria. In developing countries such as China and developed countries such as the USA, there is evidence of the high pervasiveness of antibiotic-resistant infections. However, the studies on the spread of antibiotic-resistant microorganisms that inform about the consequences are limited. The aim of our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…Antibiotic resistance can develop as a result of excessive antibiotic usage [ 3 , 42 , 43 ]. In this study, the antimicrobial resistance profile among Salmonella isolates was nearly similar to those recorded in Egypt [ 6 ], China [ 44 ], and Bangladesh [ 31 ].…”
Section: Discussionsupporting
confidence: 77%
“…Antibiotic resistance can develop as a result of excessive antibiotic usage [ 3 , 42 , 43 ]. In this study, the antimicrobial resistance profile among Salmonella isolates was nearly similar to those recorded in Egypt [ 6 ], China [ 44 ], and Bangladesh [ 31 ].…”
Section: Discussionsupporting
confidence: 77%
“…Uptaking prebiotics can improve immunity functions by increasing the population of protective microorganisms. Animal and human studies have shown that prebiotics can decrease the population of harmful bacteria by Lactobacilli and Bifidobacteria [44].…”
Section: The Probiotics: a Dynamic Relationship With Gut Microbiotamentioning
confidence: 99%
“…Antibiotics work on bacteria by interfering with crucial survival processes such as cell wall formation and suppressing the creation of important proteins, DNA, and RNA. Bacteria, on the other hand, have the inherent ability (developed from millennia of competition) to adapt rapidly through mutations and DNA transfer (through horizontal gene transfer) and it can also arise through diverse mechanisms [ 31 ], such as mutations in acquired genes, modifications leading to impermeable antimicrobial targets, enzymatic degradation or hydrolysis, and bacteria living in biofilms [ 32 ]. In addition bacterial biofilms and intracellular bacteria also contribute greatly to AMR due to drug delivery barriers, preventing the entry of drugs, expelling drugs through active efflux, mutating drug targets, and enzymatically inactivating drug function [ 33 , 34 ] to counter the threat posed by these antimicrobials.…”
Section: Antibiotics and Amrmentioning
confidence: 99%